Coaxially Fabricated Dual‐Drug Loading Electrospinning Fibrous Mat with Programmed Releasing Behavior to Boost Vascularized Bone Regeneration. Issue 16 (19th June 2022) - Cui, Jinjie; Yu, Xingge; Yu, Bin; Yang, Xiuyi; Fu, Zeyu; Wan, Jianyu; Zhu, Min; Wang, Xudong; Lin, Kaili
Abstract: In clinical treatment, the bone regeneration of critical‐size defects is desiderated to be solved, and the regeneration of large bone segment defects depends on early vascularization. Therefore, overcoming insufficient vascularization in artificial bone grafts may be a promising strategy for critical‐size bone regeneration. Herein, a novel dual‐drug programmed releasing electrospinning fibrous mat (EFM) with a deferoxamine (DFO)‐loaded shell layer and a dexamethasone (DEX)‐loaded core layer is fabricated using coaxial electrospinning technology, considering the temporal sequence of vascularization and bone repair. DFO acts as an angiogenesis promoter and DEX is used as an osteogenesis inducer. The results demonstrate that the early and rapid release of DFO promotes angiogenesis in human umbilical vascular endothelial cells and the sustained release of DEX enhances the osteogenic differentiation of rat bone mesenchymal stem cells. DFO and DEX exert synergetic effects on osteogenic differentiation via the Wnt/ β ‐catenin signaling pathway, and the dual‐drug programmed releasing EFM acquired perfect vascularized bone regeneration ability in a rat calvarial defect model. Overall, the study suggests a low‐cost strategy to enhance vascularized bone regeneration by adjusting the behavior of angiogenesis and osteogenesis in time dimension. Abstract : Fabrication of a novel dual‐drug loading coaxially electrospinning fibrous mat with programmed release behavior, in which the shell layer is loaded deferoxamine and the core layer is loaded dexamethasone, which has dual functions on angiogenesis and osteogenesis, and synergistically promotes osteogenic differentiation via the Wnt/ β ‐catenin signaling pathway and boosts vascularized bone regeneration in vivo.